Wind Affected Density Current Profile in a Small Semi-Enclosed Water Body - B. S. Purwanto (Institute of Research and Community Outreach - Petra Christian University, 2009)
Density current is a type of current that occurs when fluid flow enters a fluid body of different density. The density difference introduces stratification state that requires treatment in the parameterization of turbulence. Due to the geometric shape of location of this study, which is considerably small semi-enclosed water body, a Quasi-Equilibrium Turbulent Energy (QETE) model was selected. QETE was selected because of its convenient parameterization of wind induced breaking wave effect on turbulence. Two equations of the model, turbulence kinetic energy and turbulence macro length scale, were discretized and implemented into a three-dimensional hydrodynamic model. Application to density current simulation in the location of study was then carried out using the resulted model. To show how effective formulation of wind induced breaking wave effect would be, three parameterizations of turbulence were considered. They include QETE model with and without breaking wave effect boundary conditions (BC), and constant eddy viscosity turbulence parameterizations. It was clear from the simulation results that wind induced breaking-wave effect on the density current is quite significant.